Type I interferon score is associated with the severity and poor prognosis in anti-MDA5 antibody-positive dermatomyositis patients - Qian, Jinjing; Li, Rui; Chen, Zhiwei; Cao, Zehui; Lu, Liangjing; Fu, Qiong (Frontiers in Immunology, 2023)
Objectives: To investigate the clinical significance of the interferon (IFN) score, especially the IFN-I score, in patients with anti-melanoma differentiation-associated gene 5 (MDA5) antibody-positive dermatomyositis (anti-MDA5+ DM). Methods. We enrolled 262 patients with different autoimmune diseases, including idiopathic inflammatory myopathy, systemic lupus erythematosus, rheumatoid arthritis, adult-onset Still’s disease, and Sjögren’s syndrome, as well as 58 healthy controls. Multiplex quantitative real-time polymerase chain reaction (RT-qPCR) using four TaqMan probes was used to evaluate type I IFN-stimulated genes (IFI44 and MX1), one type II IFN-stimulated gene (IRF1), and one internal control gene (HRPT1), which were used to determine the IFN-I score. The clinical features and disease activity index were compared between the high and low IFN-I score groups in 61 patients with anti-MDA5+ DM. The associations between laboratory findings and the predictive value of the baseline IFN-I score for mortality were analyzed. Results. The IFN score was significantly higher in patients with anti-MDA5+ DM than in healthy controls. The IFN-I score was positively correlated with the serum IFN-α concentration, ferritin concentration, and Myositis Disease Activity Assessment Visual Analogue Scale (MYOACT) score. Compared with patients with a low IFN-I score, patients with a high IFN-I score showed a higher MYOACT score, C-reactive protein concentration, aspartate transaminase concentration, ferritin concentration, plasma cell percentage, and CD3+ T-cell percentage, as well as lower lymphocyte, natural killer cell, and monocyte counts. The 3-month survival rate was significantly lower in patients with an IFN-I score of >4.9 than in those with an IFN-I score of 4.9 (72.9% vs. 100%, respectively; P = 0.044). Conclusion. The IFN score, especially the IFN-I score measured by multiplex RT-qPCR, is a valuable tool to monitor disease activity and predict mortality in patients with anti-MDA5+ DM.